2022
DOI: 10.1186/s12887-022-03294-2
|View full text |Cite
|
Sign up to set email alerts
|

Throat carriage rate, associated factors, and antimicrobial susceptibility pattern of group A Streptococcus among healthy school children in Jigjiga City, Eastern Ethiopia

Abstract: Background Group A Streptococcus has been recognized as an important human pathogen and it remains among the top ten causes of mortality from an infectious disease. Group A Streptococcus throat carriage plays an important role in the development of infection and transmission to contacts. In Ethiopia, there is little information about screening of children for group A Streptococcus carriage. Objective This study was aimed to assess the magnitude of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The existing result recorded that the prevalence rate of S. pyogenes carriage was detected among medical students who lived in a single house (2.9%), less than 5 individuals lived per room (1.5%), and less than 5 children lived in a household (2.3%). It was found that children from families with more than eleven members had a four-fold greater chance of carrying GAS than children from families with fewer members [27].…”
Section: Discussionmentioning
confidence: 99%
“…The existing result recorded that the prevalence rate of S. pyogenes carriage was detected among medical students who lived in a single house (2.9%), less than 5 individuals lived per room (1.5%), and less than 5 children lived in a household (2.3%). It was found that children from families with more than eleven members had a four-fold greater chance of carrying GAS than children from families with fewer members [27].…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 62 In our study, all the GAS isolates were susceptible to penicillin, which is also reported by several studies worldwide. 30 , 31 , 41 , 45 , 46 Hence, given its narrow spectrum, low cost, and efficacy in preventing strep throat complications such as RHD and PSGN, penicillin remains the drug of choice for treating GAS pharyngitis. 17 Our findings reveal that vancomycin 4.3% and ceftriaxone 13% have reduced susceptibility against GAS causing pharyngitis.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates also showed 95.7% susceptibility to chloramphenicol, which is consistent with reports from other studies in Ethiopia. 30 , 71 The acquisition of chloramphenicol O-acetyltransferase (CAT) enzymes or the presence of active efflux mediated by specific transporters is highly associated with chloramphenicol resistance. Target modifications are also possible through point mutations or cfr (chloramphenicol–florfenicol-resistance)-mediated methylation in 23S rRNA (ribosomal ribonucleic acid).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a study by Barsenga et al [27] revealed a high rate of GAS among those who had a history of hospitalization (13.5%). Also, children who lived with a family member who had a sore throat were twice as likely to colonize group A Streptococcus (GAS) than children who did not have a primary case or sore throat in their household [27].…”
Section: Discussionmentioning
confidence: 99%